2019
DOI: 10.1111/jcpt.12798
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of post‐operative hyperalgesia in a heroin‐addicted patient on methadone maintenance

Abstract: Summary What is known and objective The exponential increase in chronic opioid consumers resulted in more challenges regarding post‐operative pain management. Considering the usual hyperalgesic response to pain and the increased opioid‐tolerance, a multidrug approach should be desirable. Case description We described the strategy in pain management of a patient receiving methadone maintenance treatment, who underwent surgery associated with moderate post‐operative pain. The combination of balanced general anae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Our search identified 324 unique articles, of which 12 articles 11,13,14,[23][24][25][26][27][28][29][30][31] met our inclusion criteria (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our search identified 324 unique articles, of which 12 articles 11,13,14,[23][24][25][26][27][28][29][30][31] met our inclusion criteria (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…All studies were retrospective (3 studies with a control group and 9 without): 4 studies examined patients with OUD taking buprenorphine, 14,24,28,30 5 examined those taking methadone, 11,[25][26][27]31 1 examined a patient taking naltrexone, 29 and 2 examined a mixed group of medications. 13,23 Four studies examined those with emergency conditions, 14, 24-26 7 examined those undergoing planned surgery, 13,23,[27][28][29][30][31] and 1 examined a mixed group of emergency and surgical patients. 11 Study size ranged from 1 to 134 participants, and studies were conducted in hospitals/tertiary care centers, specialized pain centers, and outpatient addiction treatment clinics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In situations when methadone is not available, the conversion of methadone to any opioid can be performed; however, the conversion calculations may not be bidirectional due to the long half-life of methadone ( 21 ). A multimodal approach ( 16 , 27 ) including the perioperative infusion of ketamine ( 28 , 29 , 30 ), clonidine ( 31 ), and the use of regional anesthesia ( 32 ) should be considered. In a retrospective cohort study performed by Macintyre et al ( 26 ), methadone opioid substitution therapy was continued and it showed the efficacy and safety of PCA opioids for the management of postoperative pain ( 26 ).…”
Section: Summary Of Evidencementioning
confidence: 99%